Sugarcane Productivity as a Function of Zinc Dose and Application Method - Silva, Marcelo de Almeida [UNESP]; Germino, Gabriel Henrique [UNESP]; de Holanda, Lucas Almeida; Oliveira, Laura Costa [UNESP]; Santos, Hariane Luiz [UNESP]; Sartori, Maria Márcia Pereira [UNESP] (MDPI, 2022)
Sugarcane is one of the main crops in Brazilian agriculture. It has high economic and productive potential, but its current productivity is still lacking due to poor nutritional management in both the soil and the plant. Zinc (Zn) directly affects tillering and plant growth, which are critical factors to sugarcane productivity and ratoon longevity. Thus, this research aimed to evaluate the effects of Zn chelate doses (185, 260, and 330 g ha−1) and two application methods (furrow and foliar applications) on the tillering, yield, and quality of sugarcane. The Zn chelate fertilization via furrow at a dose of 330 kg ha−1 provided increases of 13.59%, 17.6%, and 17.0% in stalk height (SH), stalk (TSH) productivity, and sugar (TPH) productivity, respectively. In contrast, Zn foliar application at a dose of 260 g ha−1 provided increases of 3.71%, 20.7%, and 17.0% in SH, TSH, and TPH, respectively. The optimal Zn chelate fertilization in sugarcane cultivation can be performed at a dose of 330 g ha−1 via furrow application at planting or at a dose of 260 g ha−1 via foliar application 145 days after planting.
Keywords: chelate; liquid fertilizer; micronutrient; Saccharumspp; yield